Improvement of Small and Medium Businesses Through the Utilization of Good Human Resources Management - Alifian Nugraha; Avid Leonardo Sari; Irwandi (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2022)
The importance of national development to improve the quality of people’s lives is quite essential because the welfare of its people indeed measures the development of a country. One of the steps to improve this welfare is to improve the quality of SMEs. Enhancing SMEs’ quality can be implemented by utilizing good human resource management. This study aims to see how the state operates human resource management to be able to increase SMEs owned by the community. This research will be carried out using various data obtained from the results of the study and previous studies that are still related to this research. This study found that weak human resource management often causes SMEs to be afraid to use new technologies, so their development is relatively slow. With the government’s intervention in improving the management of existing human resources, it is hoped that SMEs in Indonesia can develop quite quickly.